Dario Fo: The Articulate Representative of the Inarticulate Culture - Ahmad, Farhan; Alam, Sohaib (Journal of Education Culture and Society, 2022)
Aim. The proposed study examines the subversive polemics of Fo’s theatre which serves as a catalyst for social, political and cultural change. It aims to foreground the revolutionary politics of Fo who uses theatre to combat the oppressive system bringing to fore the working-class struggle for a classless society. The present study will be done with the help of the analysis of Fo’s select plays. These plays will be interpreted using the Gramscian framework of cultural consensus, an enabling provision of authority and control and the role of intellectuals in countering the same.Concept. The paper underlines the significance of art in facilitating a deeper understanding of the complex social realities of our world. The paper engages with the question of power and control, oppression and marginalisation as well as art and education as contextualised in Dario Fo’s theatre.Results. Fo’s use of drama to humanize the history of Italian working classes tells us about the expedience of art to enage with matters most urgent. This tells us that art and culture can be an important link in the mobilization authoritarism.Conclusion. A comprehensive discussion on power politics is presented in the paper with the aim of keeping people informed of the subtle working of these underlying structures which govern power relations in society.Originality. The originality of the study is contingent on investigating into how power is acquired, legitimised, practised, and maintained, how it can be resisted and what role art and artists play in the construction, dissemination and opposition of it.